Komparasi Financial Teknologi Syariah di Negara Indonesia dan Malaysia - Saputra, Randa Fajar; Y, Yusra; S, Syahpawi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Verse 133 of Surah Al-Baqarah in the Koran reflects an important moment in history when the prophet Yakub (Jacob) was nearing the end of his life and spoke to his children about their spiritual choices after his death. (133) Were you witnesses when death came to Jacob, when he said to his sons,